Recent advances in single-molecule fluorescence microscopy render structural biology dynamic. (December 2020) - Bacic, Luka; Sabantsev, Anton; Deindl, Sebastian
Highlights: Single-molecule fluorescence microscopy is a powerful tool to study the structural dynamics of biological macromolecules. Recent developments in multi-coordinate single-molecule FRET techniques allow for the study of more complex systems. Novel studies highlight the benefits of a close intermarriage between single-molecule and structural approaches. These developments bring us one step closer to a dynamic understanding of biological processes in atomic details. Abstract : Single-molecule fluorescence microscopy has long been appreciated as a powerful tool to study the structural dynamics that enable biological function of macromolecules. Recent years have witnessed the development of more complex single-molecule fluorescence techniques as well as powerful combinations with structural approaches to obtain mechanistic insights into the workings of various molecular machines and protein complexes. In this review, we highlight these developments that together bring us one step closer to a dynamic understanding of biological processes in atomic details.